2004
DOI: 10.1128/jvi.78.14.7852-7860.2004
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Latent Membrane Protein LMP-2A Is Sufficient for Transactivation of the Human Endogenous Retrovirus HERV-K18 Superantigen

Abstract: Superantigens are microbial proteins that strongly stimulate T cells. We described previously that the Epstein-Barr virus (EBV) transactivates a superantigen encoded by the human endogenous retrovirus, HERV-K18. We now report that the transactivation is dependent upon the EBV latent cycle proteins. Moreover, LMP-2A is sufficient for induction of HERV-K18 superantigen activity.Superantigens are pathogen-derived proteins that elicit a strong primary T-cell response from the host (reviewed in references 25 and 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 64 publications
2
54
0
4
Order By: Relevance
“…Subsequently, we demonstrated that two EBV-encoded proteins, LMP-2A and LMP-1, are each responsible for transactivating HERV-K18 env during latency (11). In the present study we have shown that HERV-K18 env is transactivated as early as when EBV first docks to hCD21 on its host cell, before the establishment of latency.…”
Section: Pkcs and Ptks Mediate Herv-k18 Env And Il-6 Transactivation supporting
confidence: 50%
See 1 more Smart Citation
“…Subsequently, we demonstrated that two EBV-encoded proteins, LMP-2A and LMP-1, are each responsible for transactivating HERV-K18 env during latency (11). In the present study we have shown that HERV-K18 env is transactivated as early as when EBV first docks to hCD21 on its host cell, before the establishment of latency.…”
Section: Pkcs and Ptks Mediate Herv-k18 Env And Il-6 Transactivation supporting
confidence: 50%
“…Efforts to understand how EBV transactivates the HERV-K18 superantigen revealed that LMP-2A and LMP-1 each contributes to the induction of the superantigen activity in latently infected cells in vitro (11). To further understand the biological significance of the superantigen, the status of the HERV-K18 env transcript was investigated during the earlier stages of the EBV infection process before the establishment of latency.…”
mentioning
confidence: 99%
“…For example, activation of NAIP via an LTR promoter may provide an avenue for germ cells to escape transitory, stress-induced apoptotic signals. LTR promoters may be particularly responsive to upregulation by cellular stresses since it has been shown that activation of human and mouse ERV LTRs can occur following stresses such as viral infection [54][55][56] and UV irradiation [57,58]. Various IAPs are expressed in human [59,60], mouse [61], and rat [62,63] germ cells or their progenitors, and it has been reported that Naip expression plays a role in mouse oocyte viability [61].…”
Section: Discussionmentioning
confidence: 99%
“…Les récepteurs des fragments du complément L'engagement des récepteurs membranaires des fragments du complément, notamment le C3b, semble aussi jouer un rôle important dans la transactivation d'HERV. En effet, les gènes de latence d'EBV, LMP (latent membrane protein)-1 et LMP-2A, qui codent des protéines membranaires impliquées dans la survie des lymphocytes B infectés [16], peuvent transactiver HERV-K18 via une interaction avec le CD21 ou CR2 (complement receptor type 2), récepteur du C3d exprimé par les lymphocytes B [17]. Cette transactivation étant quasi immédiate après l'entrée d'EBV dans les cellules, il n'est pas nécessaire qu'il y ait une réplication virale.…”
Section: Rôle De Hcmv Et Ebv Sur La Méthylationunclassified